Correlative Microscopy of Lamellar Hole-Associated Epiretinal Proliferation - Denise Compera; Enrico Entchev; Christos Haritoglou; Wolfgang J. Mayer; Felix Hagenau; Jean Ziada; Anselm Kampik; Ricarda G. Schumann (Journal of Ophthalmology)
Purpose. To describe morphology of lamellar hole-associated epiretinal proliferation (LHEP) removed from eyes with lamellar macular holes (LMH). Methods. Based on optical coherence tomography data, 10 specimens of LHEP were removed from 10 eyes with LMH during standard vitrectomy. Specimens were prepared for correlative light and electron microscopy (CLEM) using an immunonanogold particle of 1.4 nm diameter that was combined with a fluorescein moiety, both having been attached to a single antibody fragment. As primary antibodies, we used antiglial fibrillary acidic protein (GFAP), anti-CD45, anti-CD64, anti-α-smooth muscle actin (α-SMA), and anticollagen type I and type II. Results. In LHEP, GFAP-positive cells possess ultrastructural characteristics of fibroblasts and hyalocytes. They represent the major cell types and were densely packed in cell agglomerations on vitreous collagen strands. Epiretinal cells of LHEP rarely demonstrated contractive properties as α-SMA-positive myofibroblasts were an infrequent finding. Conclusion. CLEM indicates that epiretinal cells in LHEP might originate from the vitreous and that remodelling processes of vitreous collagen may play an important role in pathogenesis of eyes with LMH.